2008
DOI: 10.1038/clpt.2008.113
|View full text |Cite|
|
Sign up to set email alerts
|

Racial Differences in Blood Pressure Response to Angiotensin-Converting Enzyme Inhibitors in Children: A Meta-Analysis

Abstract: Angiotensin-converting enzyme (ACE) inhibitors are frequently used to treat hypertension in children (1). ACE inhibitors alter the balance between the vasoconstrictive, salt-retentive, and cardiac hypertrophic properties of angiotensin II and the vasodilatory and natriuretic properties of bradykinin; they also alter the metabolism of other vasoactive substances (2). Through these mechanisms, ACE inhibitors decrease systemic vascular resistance and promote natriuresis without increasing heart rate. They have pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…16 Apart from these largely pharmacokinetics-based differences, a study in the current issue 17 suggests differential effectiveness in antihypertensives, particularly angiotensin-converting enzyme inhibitors, between black and white pediatric patients, reflecting a similar trend seen in adults. Evaluation of pediatric studies conducted for 108 products between 1998 and 2005 in response to the FDA's written requests indicated that unique pediatric dosing is often necessary, reflecting growth and maturational stages of pediatric patients, and that pediatric dosing should not be determined by simply applying weight-based calculations to the adult dose.…”
Section: Drug-drug Interactions (And Genetics)mentioning
confidence: 95%
“…16 Apart from these largely pharmacokinetics-based differences, a study in the current issue 17 suggests differential effectiveness in antihypertensives, particularly angiotensin-converting enzyme inhibitors, between black and white pediatric patients, reflecting a similar trend seen in adults. Evaluation of pediatric studies conducted for 108 products between 1998 and 2005 in response to the FDA's written requests indicated that unique pediatric dosing is often necessary, reflecting growth and maturational stages of pediatric patients, and that pediatric dosing should not be determined by simply applying weight-based calculations to the adult dose.…”
Section: Drug-drug Interactions (And Genetics)mentioning
confidence: 95%
“…A meta-analysis of studies evaluating ethnic differences in children treated with ACEI suggested a difference between black and white children to the antihypertensive effects of ACEI. Black children demonstrated a lesser antihypertensive response than white children 31. ACEI are contraindicated in patients with bilateral renal artery stenosis.…”
Section: Clinical Studies Safety and Efficacymentioning
confidence: 90%
“…Beta-blockers and calcium channel blockers should be considered in patients with migraine. In general, black children and adolescents do not respond as well to ACEIs at standard doses 31. Beta-blockers must be used with caution or avoided in patients with asthma and a reliable method of birth control must be in place for sexually active adolescents on ACEs or ARBs.…”
Section: Place In Therapy and Patient Preferencementioning
confidence: 99%
“…1 Racial differences do occur and are meaningful in the response to antihypertensive agents. 2 In the current issue of JAMA Dermatology, Bhattacharya and Silverberg 3 systematically examined the efficacy of systemic treatments for atopic dermatitis in racial and ethnic minorities in the United States. In short, there is almost no evidence that any of the agents studied by the investigators are effective, safe, more effective, or less effective in these minority populations.…”
Section: The Lack Of Information In Racial and Ethnic Minorities And mentioning
confidence: 99%
“…In the closely related human pathogen Merkel cell polyomavirus, sT acts as a transforming oncoprotein in vitro because it alone is sufficient to transform rodent fibroblast cells. 2 Interestingly, this mechanism does not seem to involve protein phosphatase 2A (PP2A), which is a characteristic target of other polyomaviruses' sT antigens. Because PP2A regulates important cellular pathways, the inactivation is one of the critical steps in the polyomavirus pathomechanism.…”
Section: Binding Of the Trichodysplasia Spinulosa-associated Polyomavmentioning
confidence: 99%